Fatigue among children with a chronic disease: a cross-sectional study - Merel M Nap-van der Vlist; Geertje W Dalmeijer; Martha A Grootenhuis; Marry M van den Heuvel-Eibrink; Joost F Swart; Elise M van de Putte; Sanne L Nijhof; Kors van der Ent (BMJ Publishing Group, 2021)
Objective To determine: (1) which biological/lifestyle, psychological and/or social factors are associated with fatigue among children with a chronic disease and (2) how much each of these factors contributes to explaining variance in fatigue.Design and setting This was a cross-sectional study across two children's hospitals.Patients We included children aged 8-18 years who visited the outpatient clinic with cystic fibrosis, an autoimmune disease or postcancer treatment.Main outcome measures Fatigue was assessed using the PedsQL Multidimensional Fatigue Scale. Generic biological/lifestyle, psychological and social factors were assessed using clinical assessment tools and questionnaires. Multiple linear regression analyses were used to test the associations between these factors and fatigue. Finally, a multivariable regression model was used to determine which factor(s) have the strongest effect on fatigue.Results A total of 434 out of 902 children were included (48% participation rate), with a median age of 14.5 years; 42% were male. Among these 434 children, 21.8% were severely fatigued. Together, all biopsychosocial factors explained 74.6% of the variance in fatigue. More fatigue was uniquely associated with poorer physical functioning, more depressive symptoms, more pressure at school, poorer social functioning and older age.Conclusions Fatigue among children with a chronic disease is multidimensional. Multiple generic biological/lifestyle, psychological and social factors were strongly associated with fatigue, explaining 58.4%; 65.8% and 50.0% of the variance in fatigue, respectively. Altogether, almost three-quarters of the variance in fatigue was explained by this biopsychosocial model. Thus, when assessing and treating fatigue, a transdiagnostic approach is preferred, taking into account biological, psychological and social factors.